HEAVY METALS REMOVAL FROM WASTEWATER FROM THE LEACHING PROCESS BY NEUTRALIZATION (Natural Resources and Technology, 2023)
The leaching process has been successfully used in mining industry for 100 years. Nowadays, technologies are developed in order to prevent harmful effects of leaching process on the environment. The aim of this paper was to investigate the possibility of neutralize and remove heavy metals from the water that circulates in the leaching process. Usually, no waste water is generated in the leaching process, that is, the leaching solution is not thrown out, but reused in a closed cycle. However, in the event of an accident, ie if these waters are spilled, the neutralization process can be applied in order to raise the pH value of the water and help in the precipitation of heavy metals. This paper presents the results of studied potassium hydroxide, which proved to be a very effective neutralizer that successfully removes heavy metals.
Keywords: mine Bichim; copper; zinc; iron; lead; manganese; potassium hydroxide